Evaluation of a Group Cue-Exposure Treatment for Opiate Addicts - Labrador, Francisco J.; Bernaldo de Quirós Aragón, Mónica; De Arce, Fernando (The Spanish Journal of Psychology, 2005)
Twenty-four detoxified opiate addicts were randomized to an experimental group and a control group to evaluate efficacy of a group cue-exposure treatment to reduce or extinguish classically conditioned responses to drug-related stimuli. Assessment included psychophysiological responses (skin temperature, skin conductance level—SCL—, and heart rate) to a videotape and subjective measures (subjective craving, positive and negative affect) before and after the videotape. The experimental group received a group cueexposure program to drug-related stimuli that comprised twelve treatment sessions administered three times weekly. The treatment program significantly reduced conditioned responses to drug-related stimuli, as measured by SCL and positive affect.
Keywords: craving; cue-exposure; psychophysiological assessment; addictions